Oracle e-business suite security - Abel, John (McGraw-Hill, 2007)
Implement and Maintain Rock-Solid Security for Oracle E-Business Suite Secure Oracle E-Business Suite within organizations and across the Internet using the in-depth guidance of this comprehensive volume. Oracle E-Business Suite Security covers everything from key infrastructure, technical, and functional information to cutting-edge auditing, cryptography, and VPD techniques. Real-world scenarios and insightful tips throughout illustrate how to hacker-proof, audit, and troubleshoot your system. Plus, you'll get critical information on international regulatory standards, access to online code, and a blueprint of deployment topology.